Export activity of enterprises: a case study of a border region - Zabielska, Izabela (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: Enterprises, especially SMEs, are the backbone of the Polish economy. Their desire to develop makes them decide, among other things, to export. Particularly those located in border regions, are a challenge for the economic cohesion and economic activation of these areas. The openness of the border and the prevailing economic relations between neighbouring countries are of vital importance here. This peculiarity of the border location and the potential of the border regions of Eastern Poland (peripheral and economically underdeveloped), as well as the still existing research gap in this area justifies, among other things, taking up the topic. Aim: Identification and assessment of the state of export activity of Polish companies, with particular emphasis on the sector of small and medium-sized enterprises located in the border region. Results: The research carried out (empirical — primary and secondary — identifying the level of export activity by region in terms of quantity and value) into the dynamics and level of export activity by border regions — shows significant differentiation. This differentiation is influenced, inter alia, by the location and different historical and political conditions of the neighbours. Poland’s accession to the EU in 2004 and joining the Schengen area in 2007 resulted in completely different opportunities for the development of export activity in regions located on Poland’s western border (e.g. with Germany and thus within the European Union) than in regions located on Poland’s north-eastern border (e.g. with the Kaliningrad Oblast of the Russian Federation, where the state border is at the same time the EU border in the eastern part of Europe). This peculiarity results in the fact that there is still a lack of compact, homogeneous studies on the export activity of enterprises, especially SMEs, in relation to border regions. This is certainly still an existing research gap.